Phylogeography and Coevolution of Bamboo Mosaic Virus and Its Associated Satellite RNA - Wang, Ing-Nang; Yeh, Wen-Bin; Lin, Na-Sheng (Frontiers in Microbiology, 2017)
Bamboo mosaic virus (BaMV), a plant potexvirus, has been found only in infected bamboo species. It is frequently associated with a large, linear single-stranded satellite RNA (satBaMV) that encodes a nonstructural protein. Decades of collecting across a wide geographic area in Asia have accumulated a sizable number of BaMV and satBaMV isolates. In this study, we reconstructed the BaMV phylogeny and satBaMV phylogeny with partial coat protein gene sequences and partial genomic sequences, respectively. The evolutionary relationships allowed us to infer the phylogeography of BaMV and satBaMV on the Asian continent and its outlying islands. The BaMV phylogeny suggests that the BaMV isolates from Taiwan, unsurprisingly, are most likely derived from China. Interestingly, the newly available satBaMV isolates from China were found to be most closely related to the previously established Clade III, which is found in India. The general pattern of clustering along the China/India and Taiwan divide led us to hypothesize that the Taiwan Strait has been a physical barrier to gene flow in the past evolutionary history of both BaMV and satBaMV. Lastly, cophylogeny analyses revealed a complex association pattern between BaMV and satBaMV isolates from China. In general, closely related BaMV sequences tend to carry closely related satBaMV sequences as well; but instances of mismatching with distantly related satBaMV isolates were also found. We hypothesize plausible scenarios of infection and superinfection of bamboo hosts that may be responsible for the observed association pattern. However, a more systematic sampling throughout the geographic distribution of various bamboo species is needed to unambiguously establish the origin, movement, and evolution of BaMV and satBaMV.